American Marxism - Levin, Mark R (New York Threshold Editions, 2021)
Levin explains how the core elements of Marxist ideology are now pervasive in American society and culture: from our schools, the press, and corporations, to Hollywood, the Democratic Party, and the Biden presidency. Often cloaked in deceptive labels like "progressivism" tactics of Marxism include the widespread brainwashing of students, the anti-American purposes of Critical Race Theory and the Green New Deal, and the escalation of repression and censorship to silence opposing voices and enforce conformity. Levin exposes many of the institutions, intellectuals, scholars, and activists who are leading this revolution-- and provides ideas on how to confront them.
Include Notes
Keywords: a